The effect of oxygen tension on calcium homeostasis in bovine articular chondrocytes - Gibson John S; White Rachel (Journal of Orthopaedic Surgery and Research, 2010)
Abstract Background Articular chondrocytes normally experience a lower O2 tension compared to that seen by many other tissues. This level may fall further in joint disease. Ionic homeostasis is essential for chondrocyte function but, at least in the case of H+ ions, it is sensitive to changes in O2 levels. Ca2+ homeostasis is also critical but the effect of changes in O2 tension has not been investigated on this parameter. Here we define the effect of hypoxia on Ca2+ homeostasis in bovine articular chondrocytes. Methods Chondrocytes from articular cartilage slices were isolated enzymatically using collagenase. Cytoplasmic Ca2+ levels ([Ca2+]i) were followed fluorimetrically using Fura-2 to determine the effect of changes in O2 tension. The effects of ion substitution (replacing extracellular Na+ with NMDG+ and chelating Ca2+ with EGTA) were tested. Levels of reactive oxygen species (ROS) and the mitochondrial membrane potential were measured and correlated with [Ca2+]i. Results A reduction in O2 tension from 20% to 1% for 16-18 h caused [Ca2+]i to approximately double, reaching 105 ± 23 nM (p < 0.001). Ion substitutions indicated that Na+/Ca2+ exchange activity was not inhibited at low O2 levels. At 1% O2, ROS levels fell and mitochondria depolarised. Restoring ROS levels (with an oxidant H2O2, a non-specific ROS generator Co2+ or the mitochondrial complex II inhibitor antimycin A) concomitantly reduced [Ca2+]i. Conclusions O2 tension exerts a significant effect on [Ca2+]i. The proposed mechanism involves ROS from mitochondria. Findings emphasise the importance of using realistic O2 tensions when studying the physiology and pathology of articular cartilage and the potential interactions between O2, ROS and Ca2+.